Abundant rational solutions and conservation laws of the generalized BKP-Boussinesq equation and its dimensionally reduced equations - Kang, Zhou-Zheng; Tie-Cheng Xia; Wen-Xiu Ma (Kuwait Journal of Science, 2019)
By virtue of Hirota’s bilinear forms and a quadratic function approach, we generate novel rational analytical solutions to the (3+1)-dimensional generalized BKP-Boussinesq equation and lump solutions to its three types of dimensionally reduced equations. Moreover, we derive quite a few conservation laws for those equations by employing the rst homotopy method.